2014
DOI: 10.1093/jjco/hyu102
|View full text |Cite
|
Sign up to set email alerts
|

General Health Status and Late Effects Among Adolescent and Young Adult Survivors of Childhood Cancer in Japan

Abstract: Many adolescent/young adult childhood cancer survivors could be suffering from ongoing late effects that stem from cancer and its treatment. Overall health monitoring for childhood cancer survivors can provide indispensable benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
2
29
1
3
Order By: Relevance
“…Siblings also scored poorly on vitality compared with norms, but this study was low in scientific merit . Several studies reported similar or better functioning among siblings,but findings are tempered by methodological shortcomings (eg, unvalidated measures and poorly defined samples).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Siblings also scored poorly on vitality compared with norms, but this study was low in scientific merit . Several studies reported similar or better functioning among siblings,but findings are tempered by methodological shortcomings (eg, unvalidated measures and poorly defined samples).…”
Section: Resultsmentioning
confidence: 56%
“…Fourteen papers reported on QoL (13 quantitative, 1 mixed‐methods) . Two quantitative papers were low in sibling‐specific scientific merit .…”
Section: Resultsmentioning
confidence: 99%
“…As reported in the previous study, CCS with brain tumor or bone/soft‐tissue sarcoma had significant high and severe late effects . It is commonly assumed that most CCS have some late effects, which has a negative impact on psychosocial outcomes . In the present study, however, we found no association between the primary cancer diagnosis and CCS worries, this may be due to resilience or response shift.…”
Section: Discussionmentioning
confidence: 99%
“…Sibling data was not shown. 44% of original cohort lost to follow‐up raising issues of bias in the remaining sample;6xOzono, 2014, General Health Status and Late Effects Among Adolescent and Young Adult Survivors of Childhood Cancer in Japan Cross sectional survey‐based.CCS and siblings: (i) N = 185 CCSs (mean age 23.6); dx with cancer age <18; were >5 years since dx (mean 15.3 yrs since dx); and in remission >1 year.…”
Section: Supplementary Informationmentioning
confidence: 99%